2020
DOI: 10.32479/ijeep.8373
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Using Biogas Feeding for Fuel Cells in Malaysia

Abstract: Malaysia as a tropical country is blessed with biomass resources that can be transferred to produce biogas. Despite its plentiful supply, biogas in Malaysia still has not been fully optimised as only a small fraction of biomass from oil palms are currently being processed to produce biogas. This paper aims to identify the potential use of biogas to be fed to fuel cells, and determine the conservation of conventional resources and reduction of carbon dioxide (CO 2 ) emissions in electricity generation. Annually… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…In 2019, Malaysia could produce about 134 MW of plant capacity by using biogas as the main fuel in boilers. Currently, Malaysia only generates about 45.01 MW of biogas plant capacity [28]. It means that only 33.5% of biogas from palm oil waste is being utilised in the country's electricity generation.…”
Section: Resultsmentioning
confidence: 99%
“…In 2019, Malaysia could produce about 134 MW of plant capacity by using biogas as the main fuel in boilers. Currently, Malaysia only generates about 45.01 MW of biogas plant capacity [28]. It means that only 33.5% of biogas from palm oil waste is being utilised in the country's electricity generation.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, biogas as potential biomass energy is gradually emerging in Malaysia. It has been reported that the potential of biogas industry can reach to RM 8.3 billion (USD 2.3 billion) by year 2022, possibly contributed by different biomass sources including agricultural waste, crop residue, animal manure, domestic and household waste, amongst others [32]. Nevertheless, the installation of biogas plants in Malaysia is rather slow as compared to solar photovoltaic (PV) as well as mini hydro [33].…”
Section: Malaysian Biomass Energy: Industrial Status and Developmentmentioning
confidence: 99%
“…Therefore, an appropriate waste management system in palm oil mills can provide a clean and sustainable environment [23]. According to Shafie et al, [24], by 2030, Malaysia has the potential to generate about 1474MW of electricity by using biogas resources. This is expected to fulfil Malaysia's National Renewable Energy Policy that targets 20% of renewable energy in mixing energy generation towards 2030.…”
Section: Fig 2 Variety Of Biomass Production In Malaysiamentioning
confidence: 99%
“…These techniques constitute the process of biodegradable organic wastes. It is currently being practice in the palm oil industry and commonly applied in Malaysia due to cost-effectiveness and attractiveness of the method in relation to waste management and treatment [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. Output biogas is used in electricity generation up to 2 MW per power plant.…”
Section: Current Biogas Plants In Malaysiamentioning
confidence: 99%